Ambiance rose production and nutrient supply in soil irrigated with treated sewage - Giuliano Gabrielli; Jorge L. da Paixão; Bruno Coraucci; Adriano L. Tonetti (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Effluents from secondary sewage treatment plants may contain amount of nutrients with the potential to cause eutrophication of water bodies. One of the ways to decrease this influx of nutrients would be the agricultural reuse. Therefore, the objective of this study was to evaluate the irrigation of roses of the Ambiance variety with the effluent from an anaerobic reactor and an intermittent sand filter (nitrified effluent). The trial lasted for 152 days. The dose of nitrogen applied via effluent was 91% of the crop requirement; of phosphorus, 3.5% (very low); and of potassium, 23%. There was no difference among treatments for the evaluated variables: diameter and length of stem, diameter and length of bud, and fresh weight of flower buds. The production of floral stems was higher in treatments with effluents without conventional fertilization. It is concluded that the irrigation with a treated effluent is an alternative for the fertilization of ambiance roses.